Brand Extensions: When to Use Them - Sullivan, Mary W. (Management Science, 1992)
This empirical study investigates whether brand extensions should be introduced early or late in the life cycle of a product category. The longitudinal/cross-category sample of frequently purchased consumer brands is used to analyze how the performance of brand extensions depends on order of entry. The results indicate that early-entering brand extensions do not perform as well on average as either early-entering new-name products or late-entering brand extensions. This conclusion is based on four findings. First, the brand extensions were introduced later on average than the new-name products. Second, the early brand extensions had a lower probability of surviving than either the early-entering new-name products or the late-entering brand extensions. Third, the brand extensions earned higher market shares on average than new-name products, controlling for order of entry. Fourth, the extensions obtained smaller market share premia from entering early than did new-name products.